Two-Dimensional Transition Metal Oxide and Hydroxide-Based Hierarchical Architectures for Advanced Supercapacitor Materials - Guan, Meili; Wang, Qiuwan; Zhang, Xuan; Bao, Jian; Gong, Xuezhong; Liu, Youwen (Frontiers in Chemistry, 2020)
Supercapacitor has been widely seen as one of the most promising emerging energy storage devices, by which electricity was convert from chemical energy and stored. Two-dimensional (2D) metal oxides/hydroxides (TMOs/TMHs) is revolutionizing the way of advanced design of high performance supercapacitors because of their large number of higher theoretical specific capacitance, plenty of electrochemically active sites and feasibility to assemble in hierarchical structures by integrating with graphitic carbon, conductive polymers and so on. The achieved hierarchical structures can not only overcome the limitations of single material, but also bring new breakthroughs in performance. In this article, the research progress of 2D TMOs/TMHs and their hierarchical structures being used as supercapacitor materials is reviewed, including the evolution of supercapacitor materials, the configurations of hierarchical structures and the regulated electrical properties, as well as the existence of advantages and drawbacks. Finally, a perspective covering directions and challenges related to development of supercapacitor materials is provided.